The end of UMNO? sssays on Malaysia's dominant party - Welsh, Bridget 1967- (Strategic Information and Research Development Centre, 2016)
"The question of UMNO's future goes to the heart of Malaysia's future. Having governed Malaysia for nearly six decades, whether (and how) UMNO can tackle reasons for the decay in its public standing will shape the path ahead for all Malaysians. Views of the party are deeply polarized. Many have given up on UMNO altogether. With its party leader, UMNO President, and Prime Minister Najib Tun Razak embroiled in scandals, involving billions of ringgit, multiple legal jurisdictions and unanswered concerns about the use of funds and potential abuses of power, UMNO is facing one of the most serious crises in the party's history. UMNO is indeed at a crossroads. This book aims to contribute to understanding, broaden public debate and stimulate further research on arguably Malaysia's most important political institution."--Back cover.